Functional Outcome of Spinopelvic Fixation in Lumbosacral Pathologies - Bhandari, Pratap Babu; Kaucha, Deepak; Chaudhary, Rajesh Kumar; Barakot, Ram Krishna; Shrestha, Babu Kaji (Journal of Bharatpur Hospital, 2025)
Background Achieving stable lumbosacral arthrodesis remains a technical challenge owing to the high biomechanical stress. Spinopelvic fixation offers enhanced stability and good bony fusion. This study aimed to evaluate functional and radiological outcomes of patients who underwent spinopelvic fixation surgery at our institution. Methods We performed a retrospective analysis of patients who underwent spinopelvic fixation surgery between January 2017 and December 2021. Data was obtained from hospital registries in-person evaluations and telephone follow-up. Results Twenty patients (12 females, 8 males), aged 11–56 years, underwent spinopelvic fixation for various indications like scoliosis, trauma, infection and spondylolisthesis. Iliac screws were used in 15 cases and S2AI screws in five cases. Complications included hardware prominence (n=4), wound dehiscence (n=2), and implant failure (n=1). Four patients required implant removal due to various complications. Conclusions Spinopelvic fixation is an effective technique for stabilizing lumbosacral pathologies with excellent functional outcome.